Cytochrome P450 2C19 Poor Metabolizer Phenotype in Treatment Resistant Depression: Treatment and Diagnostic Implications - Veldic, Marin; Ahmed, Ahmed T.; Blacker, Caren J.; Geske, Jennifer R.; Biernacka, Joanna M.; Borreggine, Kristin L.; Moore, Katherine M.; Prieto, Miguel L.; Vande Voort, Jennifer L.; Croarkin, Paul E.; Hoberg, Astrid A.; Kung, Simon; et al. (Frontiers in Pharmacology, 2019)
Background Pharmacogenomic testing, specifically for pharmacokinetic (PK) and pharmacodynamic (PD) genetic variation, may contribute to better understanding baseline genetic differences in patients seeking treatment for depression, which may further impact clinical antidepressant treatment recommendations. This study evaluated PK and PD genetic variation and the clinical use of such testing in treatment-seeking patients with bipolar disorder (BP) and major depressive disorder (MDD). Methods Consecutive depressed patients evaluated at the Mayo Clinic Depression Center over a 10-year time frame (2003-2013) were included this retrospective analysis. Diagnoses of BP or MDD were confirmed using a semi-structured diagnostic interview. Clinical rating scales included the Hamilton Rating Scale for Depression, Generalized Anxiety Disorder 7 item scale, Patient Health Questionnaire-9, and Adverse Childhood Experiences Questionnaire. Clinically selected patients underwent genotyping of cytochrome P450 CYP2D6/CYP2C19 and the serotonin transporter SLC6A4. PK and PD differences and whether clinicians incorporated test results in providing recommendations were compared between the two patient groups. Results Of the 1795 patients, 167/523 (31.9%) with BP and 446/1272 (35.1%) with MDD were genotyped. Genotyped patients had significantly higher self-report measures of depression and anxiety compared to non-genotyped patients. There were significantly more CYP2C19 poor metabolizer (PM) phenotypes in BP (9.3%) vs MDD patients (1.7%, p=0.004); among participants with an s allele, the rate of CYP2C19 PM phenotype was even higher in BP (9.8%) vs MDD (0.6%, p=0.003). There was a significant difference in the distribution of SLC6A4 genotypes between BP (l/l=28.1%, s/l=59.3%, s/s=12.6%) and MDD (l/l=31.4%, s/l=46.1%, s/s=22.7%) patients (p<0.01). Among those with an s allele, the rate of CYP2C19 PM Phenotype was even higher in BP (9.8%) vs MDD (0.6%, p=0.003). Conclusion There may be underlying pharmacogenomic differences in treatment-seeking depressed patients that potentially have impact on serum levels of 2C19 metabolized antidepressants (i.e., citalopram/escitalopram) contributing to rates of efficacy vs side effect burden with additional potential risk of antidepressant response vs induced mania. The evidence for utilizing pharmacogenomics-guided therapy in MDD and BP is still developing with a much needed focus on drug safety, side effect burden, and treatment adherence.